Thermally-activated shape memory alloys for retrofitting bridge double-angle connections. (15th October 2021) - Izadi, Mohammadreza; Motavalli, Masoud; Ghafoori, Elyas
Abstract: Double-angle connections are prone to fatigue cracking in old steel bridges; however, owing to their complexity, there are not many retrofitting solutions for these details. This study proposes a retrofitting system for double-angle connections using iron-based shape memory alloys (Fe-SMAs). An innovative connection test setup equipped with an optical 3D digital image correlation (DIC) measurement system was developed. The retrofitting system included two end-anchorages set on either side of the connection. Fe-SMA strips were inserted inside the anchorages, and then were thermally activated (pre-stressed) to a temperature of 260 °C. Numerical finite element studies were performed to investigate the static behavior of the system. It was found that the activated/prestressed Fe-SMA strips not only apply a reverse positive moment on the connection (versus an undesirable negative fixity moment), but also "absorb" a portion of the negative moment, owing to the added axial stiffness. The proposed SMA-based system offers a versatile and cost-effective technique (with quick and easy installation) for bridge connections, and can significantly reduce the effects from undesirable sources of fatigue cracking.